Memoria histórica del Rodeo Chacarero de Píntag - Rivadeneira Guachamin, Cindy Paola. (2017)
The chacarero rodeo Pintag is a socio-cultural event that has been done for a long time in this location. This fact, it can be cataloged among mestizo celebrations. Based on pre-Columbian indigenous cultural practices it has built a tradition with the addition of new elements from the Spanish peasant celebrations. Pintag is a popula tion already mentioned in documents of the sixteenth century. This suggests that, as at that time and perhaps long before, was an important cultural conglomerate. Their land is suitable for growing corn, other food products and animal husbandry. Possi bly that it assisted in the origin of the celebrations that have remained until today. In the present study it is to describe the cultural components of the chacarera celebra tion. One, perhaps the most important is the figure of chagra. Obviously, from colo nial times to the present day there have been changes in various aspects. However there is something substantial that is maintained over time and is to be a celebration in a context of agricultural and livestock production. By documenting and field re search, historical developments that have taken and symbolic aspects contained in the present this tradition is exposed. As a result of this study communication actions to promote chacarero rodeo as a cultural product, in an effort to preserve the customs and traditions of this parish they are offered.